Therapy Profile and Drug Use Analysis of Chronic Kidney Disease Patients Hospitalized at Dr. H. M. Ansari Saleh Hospital: Profil Terapi dan Analisis Penggunaan Obat Pasien Chronic Kidney Disease Rawat Inap Rumah Sakit dr. H. M. Ansari Saleh - Okta Muthia Sari; Aditya Maulana Perdana Putra; Putri Nur Azizah; Sofia Sofia (Universitas Tadulako, 2023)
Background: Therapy in chronic kidney disease aims to slow down the prognosis of the disease. Objectives: Describe the types of classes and names of most drugs in treating chronic kidney disease patients based on the stage of the disease. As well as analysing the use of renal risk drugs in patients with chronic kidney disease. Material and Methods: This descriptive research will be carried out in May-June 2023. The population of this study was the entire medical record of inpatient chronic kidney disease patients at Ansari Saleh Hospital. Data analysis was performed uni variat for the study of patient characteristics and therapy profiles, while the analysis of the use of renal risk medications refers to the 2019 renal handbook. Results: A total of 51 medical records were analysed. The top five drug classes based on stages 4 and 5 include diuretics, cephalosporin antibiotics, vitamins, trace elements, angiotensin II receptor blockers, and insulin. The top five drugs received by patients based on disease stages 4 and 5 consist of furosemide, ceftriaxone, aminefronÂ®, candesartan, and insulin aspart. Renal risk drugs found in studies include drugs that need dose adjustment, are lisinopril, ramipril, cefixime, cefotaxime, meropenem, levofloxacin, ciprofloxacin, bisoprolol, diltiazem, and simvastatin. At the same time, renal-risk drugs that need to be avoided are hydrochlorothiazide and spironolactone. Conclusions: Furosemide diuretics are the most widely used therapy in stages 4 and 5. Hospitalised chronic kidney disease patients receive some renal risk drugs that, in the literature, need dose adjustment, and some need to be avoided.